Peliosis hepatis and systemic lupus erythematosus: A rare condition identified by magnetic resonance imaging - Cordeiro,Rafael Alves (2018)
Summary Peliosis hepatis is a rare benign disorder characterized by the presence of multiple cavities filled with blood with no preferential localization in the liver parenchyma. It may be related to several etiologic conditions, especially infections and toxicity of immunosuppressive drugs. To our knowledge, there are only three articles reporting the association between peliosis hepatis and systemic lupus erythematosus. In this report, we describe a case of this rare condition, highlighting the importance of magnetic resonance imaging. A short review of this subject is also presented.